2018
DOI: 10.1097/md.0000000000013757
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer laparoscopic port site metastasis

Abstract: Introduction:Laparoscopic port site metastases are a rare but clinically important cause of biochemically recurrent prostate adenocarcinoma. C-11 choline, among other prostate-specific positron emission tomography (PET) radiotracers, has improved radiologist confidence in these otherwise difficult-to-detect sites of recurrence.Patient Concerns:A 62-year-old male presented with biochemically recurrent prostate adenocarcinoma after undergoing robotic-assisted radical prostatectomy 5 years earlier.Diagnosis:C-11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A systematic review of port site metastases after robot-assisted surgery revealed histological variance in cases involving surgical device seeding, such as cervical squamous cell carcinoma and adenocarcinomas, gallbladder carcinoma, and urothelial cell carcinoma [11] . Additional primaries associated with port site metastases and seeding events after robot-assisted surgery have been described for renal cell carcinoma, prostate adenocarcinoma, and endometrial carcinoma [4] , [5] , [6] , [7] , [8] , [9] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of port site metastases after robot-assisted surgery revealed histological variance in cases involving surgical device seeding, such as cervical squamous cell carcinoma and adenocarcinomas, gallbladder carcinoma, and urothelial cell carcinoma [11] . Additional primaries associated with port site metastases and seeding events after robot-assisted surgery have been described for renal cell carcinoma, prostate adenocarcinoma, and endometrial carcinoma [4] , [5] , [6] , [7] , [8] , [9] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Pinho et al reported on a 65-year-old male with Gleason 8 (4+4) prostate adenocarcinoma (pT2c) with positive lateral margin after RALP and elevated postoperative PSA of 0.3 ng/mL 6 weeks postoperatively who underwent adjuvant radiation therapy who developed an elevated PSA associated with a right anterolateral abdominal wall lesion [8] . Lastly, Jundt et al reported on a 62-year-old male with Gleason 7 (4+3) prostate adenocarcinoma (pT2a) who developed PSA recurrence five years after undergoing RALP with 11C-choline PET/CT demonstrating avidity in the soft tissue associated with a prior laparoscopic site [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Only eight previous cases reports were identified to demonstrate peritoneal and portsite metastases following RARP. [4][5][6][7][8][9][10] We present a further four cases of peritoneal and portsite metastases following RARP, adding significantly to the published literature in highlighting this unusual occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of port-site metastasis from prostatic adenocarcinoma have been described on PET/CT with the use of 11 C-choline, 18 F-FDG, and 68 Ga-prostate-specific membrane antigen. [5][6][7][8][9] This case highlights the advantage of 18 F-fluciclovine PET/CT in evaluating suspected prostate cancer recurrence.…”
mentioning
confidence: 99%